Definition of and management strategies for areas of low pest prevalence for Queensland fruit fly Bactrocera tryoni Froggatt. (June 2015) - Dominiak, Bernard C.; Wiseman, Bronwyn; Anderson, Chris; Walsh, Bronwyn; McMahon, Matthew; Duthie, Rob
Abstract: Since the 1990's, international trade has relied on pest free areas or endemic categories as the basis for market access conditions. In pest free areas, pesticides or other control measures cannot be used until an outbreak is declared. Declaration of an outbreak suspends market access, with the region reverting to the status of an endemic area until pest free status is re-established. Under new phytosanitary measures, an area of low pest prevalence may be used as an intermediate step between pest freedom and outbreak that permits the use of control measures to prevent a breeding population establishing without suspending market access. A low pest population may therefore be tolerated on the basis that breeding and subsequent infestation of fruit is extremely improbable. In this paper, we identify the trapping levels that define areas of low pest prevalence and how this new standard might operate for Queensland fruit fly. Highlights: Queensland fruit fly is a serious pest that impacts trade. The pest is currents managed using a Code of Practice. A new trade standard uses the same thresholds of the Code. The new standard fits in-between the current pest freedom and outbreak standards. The new standard allows for the better management of pest populations.